Intellectual Resurgence for Contemporary Muslim Societies Adopting Malek Bennabi Social Change Paradigm - Jamil, Jamaliah (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2023)
This article describes the life and beliefs of Malek Bennabi, a figure who contributed and had a significant impact on Muslim society. Through his writings and ideas, Bennabi has left a legacy that inspires and motivates him to create a better future for the Muslim world. In addition, this research aims to provide a systematic literature review based on selected journals that specifically highlight Malek Bennabi's work with contemporary scholars to strengthen his intellectual legacy. The results of the systematic literature are: Bennabi's ideas about the challenges faced by Muslims, such as political or social marginalization and economic recession, can still be applied to current conditions, such as increasing corruption, Artificial Intelligence, the Internet of Things, mainly social media disruption of the principles of Muslim life. Moreover, while technology and progress often seem to come at the expense of traditional values, Bennabi's emphasis on the importance of creativity and the Islamic faith is particularly compelling. Finally, the findings of this study contribute to understanding the methodology, intellectual achievements, and their possible applications in post-modern society.